Pengaruh Pasang Surut Terhadap Fluktuasi Muka Air Dengan Pintu Ambang Tetap (Studi Kasus: Desa Bantan Tengah Kabupaten Bengkalis) - Putra, Alfis; Siswanto, Siswanto; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The irrigation system in fields at Bantan Tengah Village, Bengkalis Regency not be function maximally. It seens from the inability of the irigation channel and sluice to flow the discharge. The flood occured the paddy field around the research location become overflow. Flood analysis do with evaluate the dimension of channel and sluice then compare it with the discharge which count by Rational Method. Channel dimension analysis count by software HEC-RAS 4.0. The profile analysis do with 4 types of simulation of two return period, which is 5 years and 10 years. Result of the research show in existing condition known maximum high of the overflow occured for frequently 5 years is 72 cm at tide and 78 cm at wave then for frequently 10 years is 77 cm at tide and 82 cm at wave. The modification accomplish by change the dimension of width bottom the channel from 0,8 m to 1,5 m so it be able to overcome the flood maximally.Keywords: Flood, Rational Method, HEC-RAS 4.0